Heterosexual Rejection and Mate Choice: A Sociometer Perspective - Zhang, Lin; Liu, Shen; Li, Yue; Ruan, Lu-Jun (Frontiers in Psychology, 2015)
Previous studies about the effects of social rejection on individuals’ social behaviors have produced mixed results and tend to study mating behaviors from a static point of view. However, mate selection in essence is a dynamic process, and therefore sociometer theory opens up a new perspective for studying mating and its underlying practices. Based on this theory and using self-perceived mate value in the relationship between heterosexual rejection and mate choice as a mediating role, this current study examined the effects of heterosexual rejection on mate choice in two experiments. Results showed that heterosexual rejection significantly reduced self-perceived mate value, expectation, and behavioral tendencies, while heterosexual acceptance indistinctively increased these measures. Self-perceived mate value did not serve as a mediator in the relationship between heterosexual rejection and mate expectation, but it mediated the relationship between heterosexual rejection and mating behavior tendencies towards potential objects. Moreover, individuals evaded both rejection and irrelevant people when suffering from rejection.